Bariatric surgery and its impact on fertility, pregnancy and its outcome: a narrative review - Dg Marshita Pg Baharuddin; Alvin Oliver Payus; Ehab Helmy Abdel Malek Fahmy; Waidah Sawatan; Win Win Than; Abdel Mohsen Mohamed Ahmed Abdel Hafez; Nang Kham Oo Leik; D. Maryama Ag Daud; Mohd Nazri Mohd Daud; Zulkhairul Naim Sidek Ahmad (Elsevier Ltd, 2021)
Bariatric procedures are on the rise as a surgical treatment for morbid obesity. In reproductive age of women, bariatric surgeries will improve factors related to anovulation and lead to spontaneous fertility. Spontaneous pregnancy can happen within a year after bariatric surgery due to higher level of sex hormone binding globulin and follicular stimulating hormone and reduction in androgens level. Reduction of length of follicular phase of menstrual cycle was reported and contribute to improved ovulatory status. The major impact to pregnant women is development of small for gestational age babies due to persistent weight loss but this can be minimized by avoiding pregnancies too soon after bariatric surgery and good nutrition supplement. Risk of developing gestational diabetes mellitus and preeclampsia reduced among post bariatric surgery compared to no surgery. Another benefit observed are reduction in the risk of caesarean section and admission to neonatal intensive care unit. There are no significant changes in composition of breast milk in postpartum women without bariatric surgery and with women whom undergone surgery although more study needed to evaluate this effect. Good prenatal care, micronutrient supplement during antenatal follow up and close supervision from expert managing this pregnancy are essential component to ensure good outcome to mothers and their newborn.